THE IMPORTANCE OF CONTROL ELEMENTS IN THE DENTAL OFFICE MANAGEMENT - Iulian Costin Lupu; Elena Mihaela Cărăuşu; Norina Forna (Romanian Society of Oral Rehabilitation, 2014)
In the current economic situation statistical indicators suggest a decline in global and national dental services market under increased competition. So we must take a cost-effective and strengthening market position. Thus it is recommended that the management office to focus on retention and follow active patients and a system of quality control of treatments. In order to achieve these objectives must monitor certain type of control elements medical, economic, management and promotion.